PERILAKU MUYAK LATING DI KALANGAN SANTRI PONDOK PESANTREN AN-NURIYAH SUMENEP MADURA - cs, Ibrahim (Humanis; Volume 2. No. 2. Pebruari 2013, 2013)
Muyak lating behavior that occurred in the boarding school due to the factors that influence it, namely, boarding space is too tight to limit students to carry out their activities, the lack of communication with the opposite sex so homogeneous pattern of relationships, and the strong influence of friends because doing muyak lating behavior students can live safely and comfortable, lots of friends and be popular in boarding and can be recognized. The shape of muyak lating behavior is a guarantee of protection received by students who want to do muyak lating the behavior of the seniors, who eventually became the needs and behaviors become habits. From habit-going closeness and emotional intimacy arises mutual love between each other. Negative implications arising muyak lating behavior is a lack of interest in learning students, whereas positive implications can give fame to the students themselves who muyak lating behavior and also to close friends.
Keywords: Behavior Muyak lating, Rasta, and Boarding School